Serial changes in the T1 magnetic relaxation parameter after myocardial infarction in man. Issue 1 (January 1988) - Been, M; Smith, M A; Ridgway, J P; Douglas, R H; de Bono, D P; Best, J J; Muir, A L
Abstract : A low field resistive nuclear magnetic resonance imaging system (0.08 Tesla) was used to study the in vivo changes in the relaxation parameter T1 of the left ventricular myocardium from the first day to six months after acute myocardial infarction in 41 consecutive patients admitted to a coronary care unit. T1 maps were constructed from transverse and coronal images at various times after infarction. Thrombolytic treatment had been successful in 28 patients. Thirty three of the 34 patients studied within two weeks of infarction had a significantly increased T1 value but this developed only after the third day in four. At day 1-3 the mean (1 SD) maximum T1 was 413 (29) ms (n = 23) compared with 430 (41) ms (n = 22) at day 4-7, 433 (35) ms (n = 24) at day 8-14, 420 (34) at one month (n = 22), 388 (39) (n = 20) at three months, and 361 (24) (n = 14) at six months. The number of regions of interest with an increased T1 followed a similar time course. Although the increase in T1 measured at three months correlated with the initial maximum creatine kinase and with the left ventricular ejection fraction measured at one month, the number of regions with abnormal T1 from day 4 through to one month correlated best with left ventricular ejection fraction. There was no significant difference in T1 between patients with or without reperfusion. The rise in T1 over the first few days together with the prolonged time course of T1 increase suggests that the increase in T1 may reflect cellular infiltration as much or more than tissue oedema.